PERNIKAHAN BEDA AGAMA DALAM KONTEKS KEINDONESIAAN (Kajian Terhadap Q.S. Al-Baqarah: 221, Q.S. Al-Mumtahanah: 10 dan Q.S. Al-Maidah: 5) - Ulummudin Ulummudin; Azkiya Khikmatiar (Mafatih, 2021)
Abstract This article mainly discusses about different religion marriage issue which is already exist in the life of the community. The issue appears because nowadays, the relationship between male and female has no limitations either in terms of the tribe, nation, or even religion, especially in the Indonesia context. In addition, the Qur'an responds specifically about different religion marriage in three different verses namely Q.S al-Baqarah: 221, Q.S al-Mumtahanah: 10, and Q.S al-Maidah: 5. Textually, these three verses seem to have contradictory meaning. However, all of them have their own context. The first verse discusses about the prohibition to marry polytheist people, the second verse is the prohibition to marry a kaafir, and the third verse is the approval to marry a women of the book. All those terms have different meanings. In the Indonesia context, the meaning of “People (women) of the book” covers not only Jews and Christians, but also others; i.e. those who have the book and their teaching come from the Prophet. Therefore, the approval of difference religion marriage is also valid for the religion other than Jewish and Christian, such as Buddhism, Hinduism, and Kong Hu Chu.